Suppression of persistent atrial fibrillation by genetic knockdown of caspase 3: a pre-clinical pilot study - Trappe, Kerstin; Thomas, Dierk; Bikou, Olympia; Kelemen, Kamilla; Lugenbiel, Patrick; Voss, Frederik; Becker, Rüdiger; Katus, Hugo; Bauer, Alexander (European heart journal, 2013)
Atrial fibrillation (AF) is linked to cardiomyocyte apoptosis, leading to atrial remodelling and reduction in electrical conduction velocity. We hypothesized that genetic suppression of an apoptotic key enzyme, caspase 3, would prevent the development of persistent AF by reducing apoptosis which may serve as an arrhythmogenic substrate.Atrial fibrillation was induced in domestic pigs by atrial burst pacing via an implanted cardiac pacemaker. Study animals were then assigned to receive either Ad-siRNA-Cas3 gene therapy to inactivate caspase 3 or green fluorescent protein (Ad-GFP) as a control. Adenoviruses were applied using a hybrid technique employing right and left atrial virus injection followed by epicardial electroporation to increase expression of plasmid DNA. In pigs treated with Ad-siRNA-Cas3, the onset of AF was suppressed or significantly delayed compared with controls (10.3 ± 1.2 days vs. 6.0 ± 1.6 days; P= 0.04). Electrical mapping revealed prolonged atrial conduction in the control group that was prevented by Ad-siRNA-Cas3 gene therapy. On the molecular level, Ad-siRNA-Cas3 application resulted in down-regulation of caspase 3 expression and suppression of apoptotic activity.Knockdown of caspase 3 by atrial Ad-siRNA-Cas3 gene transfer suppresses or delays the onset of persistent AF by reduction in apoptosis and prevention of intra-atrial conduction delay in a porcine model. These results highlight the significance of apoptosis in the pathophysiology of AF and demonstrate short-term efficacy of gene therapy for suppression of AF.